Metabolically obese but normal weight, metabolically healthy obesity phenotypes and metabolic – cardiovascular risk - Nowak, Maria; Grzywa, Marek (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The obesity is a risk factor for cardiovascular, cancer and general mortality. It is also an independent risk factor for atherosclerosis. The incidence of obesity-related diseases depends not only on the degree of obesity but mainly on the fat tissue deposition. It is the visceral fat tissue that plays the major role in the development of insulin resistance, impaired glucose tolerance, diabetes, hypertension and cardiovascular diseases. The research showed that the population of obese people is not homogenous in terms of metabolic profile and that a BMI is not the universal obesity indicator. In the 80s Ruderman distinguished metabolic obesity with normal weight. It is defined as an increased amount of visceral and subcutaneous abdominal fat and is associated with an increased risk of metabolic disorders. Insulin resistance and hyperinsulinemia are considered to be the fundamental disorders in this group. The coexistence of impaired carbohydrate and lipid metabolism and hypertension leads to a high risk of cardiovascular disease. The fat tissue deposition enabled also to identify the obese patients that are not at risk of insulin resistance, glucose or lipid metabolism disorders and hypertension (“metabolically healthy”). There are some studies that show the reduction of cardiovascular risk among obese patients with normal metabolic parameters. However, the current knowledge does not allow us to regard obesity with normal metabolic parameters as completely safe.